PENGARUH FEAR OF MISSING OUT TERHADAP PERILAKU PHUBBING PADA REMAJA PENGGUNA MEDIA SOSIAL - Veny Desvian Adiningsih; Lilis Ratnasari (Asosiasi Dosen Muda Indonesia, 2024)
The development of increasingly advanced technological times and the presence of the internet in Indonesia has reached hundreds of millions of users who use it for various purposes, one of which is for accessing social media, which reaches more than ninety percent, of which Indonesian teenagers in the 13-18 year age group use it the most. The aim of this research is to determine the influence of fear of missing out on phubbing behavior among adolescent social media users. The sampling techinique uses purposive sampling, the sample is 158 teenage respondents who use social media. The phubbing behavior scale compiled is based on aspects: communication disturbance and phone obsession, the fear of missing out scale compiled in this research is based on aspects: self and relatedness. This research uses a simple regression testing technique using SPSS version 25 for MacOS. The results of this research are that the hypothesis is accepted with a significance value of 0.000 (p<0.05), namely that fear of missing out has a very significant effect on phubbing behavior in adolescent social media users.